Combating climate change an agricultural perspective - Kang, Manjit S.; Banga, S. S. (CRC Press, 2013)
"The effects of climate change can already be felt around the world, and they will likely impact all facets of human civilization--from health, livelihood security, agricultural production, and shelter to international trade. Since anthropogenic factors are mainly to blame for the current trends in global warming, human intervention will be necessary to mitigate it. With 17 authoritative chapters, Combating Climate Change: An Agricultural Perspective outlines a framework for preparing agriculture for climate change, presenting the causes and consequences of climate change and possible remediation measures. With contributions from internationally recognized scientists, the chapters cover global food security, adaptation of agriculture to fulfill its greenhouse gas emissions mitigation potential, economic aspects of climate change, the soil organic carbon pool, the need for agroecological intelligence, and the development of nutrient-use-efficient crops. The text also addresses genetic mitigation of climate change effects through the development of climate-resilient crops and the use of genetic and genomic resources to develop highly productive crop cultivars, as well as the conservation of native agroecosystems. Expert contributors discuss the impacts of climate change on plant pathogens and plant disease as well as on insects and crop losses. They address abiotic stress resistance, conservation tillage as a mitigation strategy, and more. The final chapter demonstrates the practical use of the WorldClim and DIVA software for modeling current and future climates, using Timor Leste and India as examples. Covering a broad range of issues related to climate change and agriculture, this book brings together ideas for environmentally friendly technologies and opportunities to further increase and stabilize global agricultural productivity and ensure food security in face of mounting climate challenge"--